Quantification of regulating ecosystem services provided by weeds in annual cropping systems using a systematic map approach. (24th March 2018) - Blaix, C; Moonen, A C; Dostatny, D F; Izquierdo, J; Le Corff, J; Morrison, J; Von Redwitz, C; Schumacher, M; Westerman, P R
Summary: Ecosystem services have received increasing attention in life sciences, but only a limited amount of quantitative data are available concerning the ability of weeds to provide these services. Following an expert focus group on this topic, a systematic search for articles displaying evidence of weeds providing regulating ecosystem services was performed, resulting in 129 articles. The most common service found was pest control and the prevailing mechanism was that weeds provide a suitable habitat for natural enemies. Other articles showed that weeds improved soil nutrient content, soil physical properties and crop pollinator abundance. Weeds were found to provide some important ecosystem services for agriculture, but only a small number of studies presented data on crop yield. Experimental approaches are proposed that can: (i) disentangle the benefits obtained from ecosystem services provisioning from the costs due to weed competition and (ii) quantify the contribution of diverse weed communities in reducing crop competition and in providing ecosystem services. Existing vegetation databases can be used to select weed species with functional traits facilitating ecosystem service provisioning while having a lower competitive capacity. However, for services such as pest control, there are hardly any specific plant traits that have been identified and more fundamental research is needed.